ANALISIS PRAKTIK MODERASI BERAGAMA DI SDK RUTENG V DALAM PERSPEKTIF PENDIDIKAN MULTIKULTURAL - Maria Merlina Dhiu; Agustina Ade Putri Mana; Maria Eudoksia Anu (Pastoralia, 2026)
This study aims to examine the implementation of religious moderation in the elementary school environment, particularly at SDK Ruteng V, as an effort to build students’ characters that are tolerant, inclusive, and capable of living harmoniously within diversity. The background of this research is based on the reality of Indonesia as a multicultural country facing challenges in maintaining interreligious harmony, making religious moderation an important strategy promoted by the Ministry of Religious Affairs of the Republic of Indonesia. This study is expected to provide a concrete description of the implementation of religious moderation values in elementary education environments and the contribution of multicultural education in shaping students’ tolerant character. This research employed a qualitative approach using a literature study method combined with contextual analysis of religious moderation practices at the school. The findings indicate that religious moderation at SDK Ruteng V has been implemented through the integration of tolerance values in learning activities, habituation of attitudes in daily life, teacher role modeling, and the support of an inclusive school culture. Concrete practices such as joint prayers according to each student’s beliefs, inclusive religious activities, multicultural-based learning, and cooperation in heterogeneous groups are part of the best practices in instilling religious moderation values. However, this study also found challenges in the form of majority group dominance that potentially limits the participation of minority groups and affects students’ social interactions. Therefore, continuous strategic efforts are needed through strengthening inclusive school policies, enhancing the role of teachers, and providing equal participation opportunities for all students. Thus, the implementation of religious moderation at SDK Ruteng V can serve as a model of good practice in creating a harmonious educational environment and supporting the formation of a generation that respects diversity.